1995
DOI: 10.1038/bjc.1995.230
|View full text |Cite
|
Sign up to set email alerts
|

Flunarizine enhancement of melphalan activity against drug-sensitive/resistant rhabdomyosarcoma

Abstract: Summanr Flunarizine. a diphenylpiperazine calcium channel blocker. is known to increase tumour blood flow. It also interferes with calmodulin function. repair of DNA damage and drug resistance associated with P-glvcoprotein. Flunarizine was tested for its ability to modulate either cyclophosphamide-or melphalaninduced growth delay for a drug-resistant rhabdomyosarcoma xenograft (TE-671 MR) and the drug-sensitive parent line (TE-671). in which P-glycoprotein is not involved in the mechanism of drug resistance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Our top scoring ligands screened through our virtual screening protocol included previously reported potent ABCB1 and ABCG2 inhibitors imatinib 28 and a weak inhibitor NVP-BHG712 29 . flunarizine 30 , and ABCB1 substrate baicalin 31 . These results indicated great potential and validity of our screening protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Our top scoring ligands screened through our virtual screening protocol included previously reported potent ABCB1 and ABCG2 inhibitors imatinib 28 and a weak inhibitor NVP-BHG712 29 . flunarizine 30 , and ABCB1 substrate baicalin 31 . These results indicated great potential and validity of our screening protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin protects neuroblastoma cells from flunarizine-induced cytotoxicity by preventing mitochondrial depolarization and, presumably, the subsequent activation of the caspase cascade. Flunarizine also sensitizes leukemia cells to vincristineinduced cell death [11] and ovarian carcinoma cells and rhabdomyosarcoma cells to melphalan-induced cytotoxicity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Horsman et al (1996) have shown that tumour blood flow changes brought about by nitro-L-arginine lasted no more than an hour, whereas the changes in redox status reported by Wood et al (1994a) could last for up to 6 h. Thus, the underlying mechanism mediating these anti-tumour effects is likely to be a complex interaction between hypoxia induction and entrapment (distribution and pharmacokinetics). Such interactions have been shown to contribute to the potentiation of the activity of both RSU1069 and the alkylating agent melphalan using a variety of techniques for modifying blood flow to tumours (Chaplin and Acker 1987;Stratford et al, 1988;Bremner et al, 1990;Castellino et al, 1995).…”
Section: Discussionmentioning
confidence: 99%